Therapeutic Potential and Mechanisms of Mesenchymal Stem Cell and Mesenchymal Stem Cell-Derived Extracellular Vesicles in Atopic Dermatitis - He K; Zang J; Ren T; Feng S; Liu M; Zhang X; Sun W; Chu J; Xu D; Liu F (Dove Medical Press, 2024)
Kang He,1,* Jie Zang,2,* Tingting Ren,1,* Shaojie Feng,3 Mohan Liu,1 Xude Zhang,3 Wenchang Sun,2 Jinjin Chu,2 Donghua Xu,2 Fengxia Liu3 1Department of Clinical Medicine of Shandong Second Medical University, Weifang, People's Republic of China; 2Central Laboratory, Weifang People's Hospital, Shandong Second Medical University/Weifang People's Hospital, Weifang, People's Republic of China; 3Department of Allergy, Weifang People's Hospital, Shandong Second Medical University, Weifang, People's Republic of China*These authors contributed equally to this workCorrespondence: Donghua Xu; Fengxia Liu, Email flower322@163.com; wf_lfx@163.comAbstract: Atopic dermatitis (AD) is a chronic and inflammatory skin disease with intense itchiness that is highly prevalent worldwide.The pathogenesis of AD is complex and closely related to genetic factors, immunopathogenic factors, environmental factors, and skin infections. Mesenchymal stem cells (MSCs) are non-hematopoietic progenitor cells derived from the mesenchymal stroma. They have anti-inflammatory, anti-apoptotic, and regenerative properties. Numerous studies demonstrate that MSCs can play a therapeutic role in AD by regulating various immune cells, maintaining immune homeostasis, and promoting the repair of damaged tissues. The key mediators for their biological functions are extracellular vesicles (MSC-Evs) and soluble cytokines derived from MSCs. The safety and efficacy of MSCs have been demonstrated in clinical Phase I / IIa trials for AD. This paper provides a comprehensive review of the pathogenesis of AD and the currently published studies on the function of MSCs and MSC-Evs in AD, primarily including the pathogenesis and the immunomodulatory impacts of MSCs and MSC-Evs, along with advancements in clinical studies. It provides insights for comprehending AD pathogenesis and investigating treatments based on MSCs.Keywords: atopic dermatitis, mesenchymal stem cells, Th2-associated immunity, extracellular vesicle